1998
DOI: 10.2307/30142418
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Hospital Rooms Contaminated with Vancomycin-Resistant Enterococcus faecium

Abstract: Sixteen percent of hospital room surfaces remained colonized by vancomycin-resistant enterococci (VRE) after routine terminal disinfection. Disinfection with a new "bucket method" resulted in uniformly negative cultures. Conventional cleaning took an average of 2.8 disinfections to eradicate VRE from a hospital room, while only one cleaning was required with the bucket method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 12 publications
0
51
0
Order By: Relevance
“…In addition, VRE contamination has been shown to persist through 3 standard room cleanings, even with bucket-based cloth-immersion cleaning. 7 Study limitations include the lack of data regarding antibiotic use. Antibiotic exposure is associated with increased VRE shedding among carriers and increased VRE acquisition among patients exposed to carriers.…”
Section: Commentmentioning
confidence: 99%
“…In addition, VRE contamination has been shown to persist through 3 standard room cleanings, even with bucket-based cloth-immersion cleaning. 7 Study limitations include the lack of data regarding antibiotic use. Antibiotic exposure is associated with increased VRE shedding among carriers and increased VRE acquisition among patients exposed to carriers.…”
Section: Commentmentioning
confidence: 99%
“…Routinely used disinfectants such as quaternary ammonium, phenolic, and iodophor germicidals are active against VRE (224). However, several studies have shown improved rates of VRE surface eradication with enhanced disinfection involving a more thorough application of the disinfectant to the surface by drenching either the surface or the cleaning rag (42,305).…”
Section: Vancomycin-resistant Enterococcusmentioning
confidence: 99%
“…Environmental sampling studies have isolated VRE from most surfaces found in rooms that previously housed infected patients, such as patient gowns, bedside rails, floors, doorknobs, and blood pressure cuffs (12). Enterococcus has been shown to persist for as long as 4 months on surfaces, and in a clinical setting, VRE was shown to persist through an average of 2.8 standard room cleanings, thereby acting as a continual source for possible transmission (40,41). Recent studies involving environmental surveillance suggest that admission to a room previously occupied by a patient with VRE infection was associated with a significant increased risk for VRE acquisition by subsequent patients (hazard ratio, 4.4) (42).…”
Section: Enterococcus Spp In the Health Care Settingmentioning
confidence: 99%